Quadricuspid Aortic Valvulopathy and Acute Type A Aortic Dissection - Klassen, Sheila L.; Hutchison, Stuart J. (AORTA, 2019)
This case report describes a 55-year-old male who presented with acute Type A aortic dissection. He underwent emergent surgical repair, and his intraoperative transesophageal echocardiography revealed a quadricuspid aortic valve. His aortic root measured 45 mm. Quadricuspid aortic valves have previously been associated with aortic root dilation. This case illustrates the possible association of quadricuspid aortic valves with aortic dissection, similar to what is described with bicuspid valves.
Keywords: quadricuspid aortic valve; aortic dissection; aortopathy; ascending aorta